Experimental and theoretical investigations on axial crushing of aluminum foam-filled grooved tube. (15th October 2019) - Yao, Ru-yang; Zhao, Zhen-yu; Hao, Wen-qian; Yin, Guan-sheng; Zhang, Bei
Abstract: Circular tube with external wide grooves has been defined as "Type B" grooved tube in the previous research. However, there have been few studies highlighting the effects of aluminum foam filling and material of "Type B" grooved tube. In the present, axial crushing behaviors of aluminum foam-filled 304 stainless steel "Type B" grooved tube are investigated. Quasi-static axial crushing tests are conducted to examined the deformation modes and energy absorption performance of foam-filled uniform/thickness gradient grooved tube with weak/strong thick-walled section. Experimental results show that the foam filling and thickness gradient configuration have a more obvious effect on energy absorption characteristics of grooved tube with weak thick-walled section. A novel analytical model is put forward by taking the strain hardening effect and effective crushing distance into consideration. Compared with the previous researches, the theoretical predictions in this study are in better agreement with the experimental results. Moreover, by comparing the experimental results of 304 stainless steel and 2A12 aluminum grooved tube, it can be concluded that the mean crushing force, crushing force efficiency and structural effectiveness of steel grooved tube are 205%, 56% and 27% on average higher than those of aluminum grooved tube.